2018
DOI: 10.1016/j.jnoncrysol.2018.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Non-Newtonian behavior of solid-bearing silicate melts: An experimental study

Abstract: The non-Newtonian behavior and its mechanism have not been clarified for the solid-bearing metallurgical slags, leading to difficulties in the modeling of viscosity. In this study, the viscosity of an industrial BOF slag with different contents of Al2O3 was measured via a rotational type rheometer at various shear rates. The crystal fraction was examined by characterizing the water-quenched samples.The results demonstrate that the slags exhibit non-Newtonian behavior for solid fractions exceeding a critical va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…viscosity), several models have been developed [8][9][10]. Although viscosity of fully liquid slag systems can be calculated sufficiently, its calculation for partly crystalline slag systems are of greater challenge [6,11]. Recent studies [12][13][14][15] indicated the impact of crystallisation on the slags viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…viscosity), several models have been developed [8][9][10]. Although viscosity of fully liquid slag systems can be calculated sufficiently, its calculation for partly crystalline slag systems are of greater challenge [6,11]. Recent studies [12][13][14][15] indicated the impact of crystallisation on the slags viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…Slag It was reported that solid-bearing slag exhibit various non-Newtonian flow characteristics with increasing solid fraction. [15][16][17] As shown in Fig. 9, the slag 1 and 4 display a linear relationship between rotational speed (shear rate) and percent torque (shear stress) at 1 600°C, indicating a Newtonian behavior.…”
Section: Non-newtonian Flow Behavior Of Solid-bearingmentioning
confidence: 83%
“…This nonlinear relationship represents the higher viscosity of hydrogels which is a strong indication on the impact of cross-linking [22]. The viscosity of a shear thinning liquid has an inversely proportional relationship with the shear rate, whereas a shear thickening liquid has a directly proportional relationship between viscosity and the shear rate [37]. Pseudoplastic nature is important for topical formulations that have viscous behaviour under static conditions; nevertheless, this viscous behaviour tends to decrease at a higher shear rate which results in better spreadability and improves the drug permeation of specific substances upon topical application [11].…”
Section: Sem Morphologymentioning
confidence: 99%